(untitled) (Marketing Journal, 2025)
This article studies the state of production at industrial enterprises of Uzbekistan. Important conclusions are drawn by using various research methods, such as statistical analysis and expert assessment, to analyze the state of production at enterprises of the food industry of Uzbekistan. The article develops recommendations for modernizing production processes, increasing export potential, and ensuring the sustainable development of the food industry.